“Recursos audiovisuales para el desarrollo del sociodrama” - Chiluisa Marcalla, Lourdes Viviana (2021)
Educating in the information and communication society requires changes in the way of teaching and learning, with the purpose of carrying out knowledge construction processes. Thus, audiovisual resources are currently widely used instruments in the classroom, especially in this time of virtual education. These elements acquire an important role in the development of the teaching-learning process by transmitting information through different channels. Teachers need to increase the didactic resources they use to teach their classes. Not only use the blackboard, textbooks, only resources that lead to students feel bored and do not concentrate properly, feeling unmotivated. This study seeks to elaborate an audiovisual resource through the use of stories for the development of sociodrama in the teaching and learning process. The methodology corresponds to qualitative research also supported by descriptive and documentary research, qualitative approach, inductive method because it seeks to understand the points of view of the subjects investigated on the facts investigated, how teachers perceive reality from delving into their experiences and opinions. The techniques used were observation and interview, which allowed to collect data on the didactic resources, its instrument was the observation guide that was applied in the didactic process and the interview guide that also allowed to collect information from teachers for the construction of a video as an audiovisual resource for the sociodrama. After detecting the research problem, it was established as a proposal to elaborate a video with educational content using stories about respect to improve teaching in "Jatari Unancha" Educational Unit. For which three stages were planned for the audiovisual production: Pre-production, production and post-production. Since the use of audiovisual teaching resources will help the teacher's work to motivate and guide the learning of students so that they feel confident and willing to learn under the guidance of the teacher as a facilitator. In the same way, the sociodrama motivates the active participation of the student and the reflection on the value of respect that is experienced and contrasted from different aspects.